The Exemption of Punishment and Criminal Responsibility According to Islamic Criminal Law - Chifa Azyana Adly meknesya; Viennalia Rizti Putri; Sarah Rubina Ilham (ISNU Sumatera Utara, 2024)
The abolition of punishment and criminal liability in Islamic criminal law is a concept that demonstrates the flexibility of sharia in realizing justice and public welfare. This issue is important because in practice, Islamic criminal law is often perceived as a rigid and repressive system, even though normative mechanisms exist that allow for the abolition of punishment and criminal liability under certain conditions. This study aims to analyze the legal basis for the abolition of punishment, examine the various factors causing the abolition of punishment, and explain the concepts and factors that influence the abolition of criminal liability in Islamic criminal law. This study uses a qualitative method with a normative library research approach by reviewing the literature and various related scientific references. The results show that the abolition of punishment has a normative basis in Islamic law, which includes forgiveness, repentance, lack of evidence, coercion, and other legal conditions recognized by sharia. However, the abolition of punishment does not always mean the loss of criminal liability, because in certain conditions there are still forms of legal consequences such as diyat. Meanwhile, criminal responsibility in Islamic law depends on the fulfillment of the elements of reason, awareness, and freedom of will, so that factors such as mental disorders, not yet reaching puberty, coercion, and unintentional acts can cause criminal responsibility to be dropped or reduced.